Function of the Reticuloendothelial System IV. Evidence for Two Types of Particle-Induced Reticuloendothelial Paralysis - Normann, Sigurd J. (1970)
Reticuloendothelial system (RES) phagocytosis has been quantitated after intravenous injection of two different sets of particles by determining the clearance rate of subsequently injected identical or nonidentical particles. Injection of carbon produced a biphasic RES paralysis consisting of an early transient phase followed by a delayed sustained phase. The two phases were separated by a distinct interval of greatly augmented clearance rates. The injection of aggregated albumin was followed only by a single period of depressed clearance, which corresponded to the first phase of carbon-induced inhibition. This first phase, designated immediate RES paralysis, was initiated by particle injection and its duration was related to the rate of particle removal, to the dose of particles injected, and to the presence of the particles in the circulation. The second phase, designated delayed RES paralysis, began sometime after the particles had been engulfed by the cells, was independent of the rate of particle removal, and persisted without the presence of measurable particles in the circulation. The evidence indicates that the immediate paralysis arises from a competition between the particles in the circulation, whereas the delayed paralysis arises from a cellular derangement inhibitory to further phagocytosis. In contrast to the usual description of RES blockade as a single sustained period of depression, the present experiments indicate that the phenomenon has two phases which can be dissociated in time and mechanism.